Peru - Owings, Lisa. (Minneapolis, MN : Bellwether Media, 2012)
Introduces young readers to the geography and culture of Peru.
Where is Peru? -- The land -- Cloud forests -- Wildlife -- The people -- Daily life -- Going to school -- Working -- Playing -- Food -- Holidays -- Machu Picchu.
Includes bibliographical references (p. 31) and index.
3.9
K-3
Keywords: Peru -- Juvenile literature; Peru; Peru; Readers (Elementary)